Continuous, dynamic and steady state simulation of the reflux classifier using a segregation-dispersion model. (January 2018) - Syed, N.H.; Dickinson, J.E.; Galvin, K.P.; Moreno-Atanasio, R.
Highlights: The Reflux Classifier has been modelled using computer simulations. The simulations were based on the segregation-dispersion equation. A total of 42 different particle species have been simulated. Partition curves have shown good agreement with the experimental data. The model also predicted the results at high throughputs. Abstract: A 2D continuous segregation-dispersion model incorporating a laminar- shear separation mechanism has been developed to describe the Reflux Classifier (RC). The RC, which consists of a fluidization zone, and a system of closely-spaced inclined channels, is now widely used to achieve gravity separation of a broad range of commodities. The narrow inclined channels promote the laminar-shear mechanism, leading to the selective shear-induced lift of low density particles, while allowing the fine and denser particles to deposit onto the inclined surfaces, and slide downwards. This mechanism allows a sharp density-based separation. The simulation results of this study have been validated using previously published experimental data. A total of 42 particle species were used in the simulations, corresponding to 6 different sizes and 7 different densities for each particle size, covering the particle size range of −2.0+0.125 mm. Simulation partition curves showed good agreement with the published experimental data, including the D50 and Ep values over the particle size range −2.0+0.25 mm. The model has also been tested to investigate the effect of high solid throughputs on the separation performance in the RC. The predictions of the fractional and cumulative ash % of the product and reject streams have been compared with the published experimental results demonstrating a good agreement and thus, the robustness of the model.